Green servitization as a means of sustainable performance: Evidence of listed manufacturing firms. Issue 1 (31st December 2022) - Oyelakin, Idris Oyewale; Johl, Satirenjit Kaur
Abstract: This study assessed green-servitization (GS) as a means of sustainable performance (SP) for publicly listed manufacturing firms in Malaysia. Manufacturing firms in recent times have faced serious challenges due to huge cost paid for environmental clean-up resulting from traditional operating system. Primary and secondary data were used for this study. Data were collected through the use of structured questionnaire. Ten (10) manufacturing companies were randomly selected, and three management staffs of the selected companies were purposely selected based on their designation to be the respondents. A simple linear regression was used to analyse the relationship between green-servitization (GS) and sustainable performance (SP). The regression result showed that the coefficient of green servitization GS is −0.040 and p = 0.247. The correlation coefficient, R = 0.218, indicates a very weak correlation between green servitization (GS) and sustainable performance (SP). The R 2  = 0.048 shows that the variation in SP is only accounted for by 4.8% of the GS. The F-test for the hypothesis testing showed that F = 1.400, p > 0.001, which implies that there is no positive significant relationship between green servitization (GS) and sustainable performance (SP). The implication of this research will be useful for policymakers to design suitable policies and industrial practitioners to improve their operations in terms of firms' sustainable performance.